2022
DOI: 10.1186/s13063-022-06090-6
|View full text |Cite
|
Sign up to set email alerts
|

A phase III randomized trial of weight loss to reduce cancer-related fatigue among overweight and obese breast cancer patients: MEDEA Study design

Abstract: Background Elevated body mass index (BMI) represents a risk factor for cancer-related fatigue (CRF). Weight loss interventions are feasible and safe in cancer survivors, leading to improved cardio-metabolic and quality of life (QOL) outcomes and modulating inflammatory biomarkers. Randomized data are lacking showing that a lifestyle intervention aimed at weight loss, combining improved diet, exercise, and motivational counseling, reduces CRF. Motivating to Exercise and Diet, and Educating to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…19 Behavioral trials of weight loss in overweight and obese BC survivors showed an impact on QOL that was particularly evident on physical function, vitality, and comorbid conditions, but most benefits tended to diminish over time, a finding that is mostly attributed to recidivism and weight regain during postintervention follow-up. [70][71][72] Ongoing randomized trials will provide additional PROs data and test whether combined interventions of weight loss (ie, with multiple components of improved diet, PA, and personalized behavioral coaching), [73][74][75] or smoking cessation programs 64,76 are able to reduce treatment-related symptoms, improve QOL, and affect clinical outcomes of BC survivors.…”
Section: Journal Of Clinical Oncologymentioning
confidence: 99%
“…19 Behavioral trials of weight loss in overweight and obese BC survivors showed an impact on QOL that was particularly evident on physical function, vitality, and comorbid conditions, but most benefits tended to diminish over time, a finding that is mostly attributed to recidivism and weight regain during postintervention follow-up. [70][71][72] Ongoing randomized trials will provide additional PROs data and test whether combined interventions of weight loss (ie, with multiple components of improved diet, PA, and personalized behavioral coaching), [73][74][75] or smoking cessation programs 64,76 are able to reduce treatment-related symptoms, improve QOL, and affect clinical outcomes of BC survivors.…”
Section: Journal Of Clinical Oncologymentioning
confidence: 99%
“…However, the average daily energy intake of the BC group during chemotherapy was 214 kcal less than that of the control group. As diet is a long-term and essential lifestyle component, and changes in dietary habits caused by chemotherapy will continue to occur during recovery, advanced stages, and survival [ 47 ]. Limited studies [ 48 , 49 ] have shown that BC patients who actively manage chemotherapy-related symptoms and actively collect nutritional information may recover better and have better quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, Motivating to Exercise and Diet, and Educating to healthy behaviuors After breast cancer (MEDEA), which investigated the impact of weight loss on CRF in overweight or obese survivors of BC, Di Meglio et al. 73 found that an elevated BMI is a risk factor for CRF in breast cancer survivors. Thus, weight loss interventions are feasible and safe for these patients, leading to improved cardiometabolic and QOL outcomes.…”
Section: Discussionmentioning
confidence: 99%